Advanced Materials for the Conservation of Stone (Springer International Publishing, 2018)
This book identifies novel advanced materials that can be utilized as protective agents for the preservation of stone. The innovative solutions to stone conservation presented here result in increased sustainability, reduced environmental impact, and increased social and economic benefits. It provides an overview of recent trends and progress in advanced materials applied to stone protection. It also explores the scientific principles behind these advanced materials and discusses their applications to diff erent types of stone preservation efforts. Essential information as well as knowledge on the availability and applicability of advanced nanostructured materials is also provided, with focus placed on the practical aspects of stone protection. Th e book highlights an interdisciplinary eff ort regarding novel applications of nanostructured materials in the advancement of stone protection. It provides insight towards forthcoming developments in the fi eld. Advanced nanostructured materials are designed and developed with the aim of being chemically, physically, and mechanically compatible with stone. Advanced materials for stone conservation that are characterized by several functional properties are considered in this book. These include the physico-chemical, protective, and morphological properties, eco-toxicity, and mechanisms of degradation. The authors present a thorough overview of cutting-edge discoveries, detailed information on recent technological developments, breakthroughs in novel nanomaterials, utilization strategies for applications in cultural heritage, and the current status and future outlook of the topic to address a wide range of scientific communities. Provides a basis for advanced materials technology assessments applied to stone conservation; Presents a thorough overview of cutting-edge discoveries and detailed information on recent technological developments, the current status, and future outlook; Covers environmental impact, sustainability, social eff ects, and economic benefits; Addresses a wide range of global scientific communities that develop and apply advanced materials for conservation purposes.